Influence of attractants and repellents on methyl group turnover on methyl-accepting chemotaxis proteins of Bacillus subtilis and role of CheW. - Hanlon, D W (1992)
The ability of attractants and repellents to affect the turnover of methyl groups on the methyl-accepting chemotaxis proteins (MCPs) was examined for Bacillus subtilis. Attractants were found to cause an increase in the turnover of methyl groups esterified to the MCPs, while repellents caused a decrease. These reactions do not require CheW. However, a cheW null mutant exhibits enhanced turnover in unstimulated cells. Assuming that the turnover of methyl groups on the MCPs reflects a change in the activity of CheA, these results suggest that the activation of CheA via chemoeffector binding at the receptor does not require CheW.